Thermal Stimulation Alters Cervical Spinal Cord Functional Connectivity in Humans. (15th January 2018) - Weber, Kenneth A.; Sentis, Amy I.; Bernadel-Huey, Olivia N.; Chen, Yufen; Wang, Xue; Parrish, Todd B.; Mackey, Sean
Highlights: Resting state functional connectivity was explored in the cervical spinal cord of healthy participants. High resolution imaging was coupled with seed-based functional connectivity analyses and graph theory-based metrics. We corroborate previous findings of bilateral motor and sensory spinal cord functional networks. We provide evidence for the presence of a unilateral sensory-motor spinal cord functional network. Thermal stimulation altered the pattern of functional connectivity and the topological properties of the functional network. Abstract: The spinal cord has an active role in the modulation and transmission of the neural signals traveling between the body and the brain. Recent advancements in functional magnetic resonance imaging (fMRI) have made the in vivo examination of spinal cord function in humans now possible. This technology has been recently extended to the investigation of resting state functional networks in the spinal cord, leading to the identification of distinct patterns of spinal cord functional connectivity. In this study, we expand on the previous work and further investigate resting state cervical spinal cord functional connectivity in healthy participants ( n = 15) using high resolution imaging coupled with both seed-based functional connectivity analyses and graph theory-based metrics. Within spinal cord segment functional connectivity was present between the left and right ventral horns (bilateral motor network), left and right dorsal horns (bilateral sensory network), and the ipsilateral ventral and dorsal horns (unilateral sensory-motor network). Functional connectivity between the spinal cord segments was less apparent with the connectivity centered at the region of interest and spanning <20 mm along the superior-inferior axis. In a subset of participants ( n = 10), the cervical spinal cord functional network was demonstrated to be state-dependent as thermal stimulation of the right ventrolateral forearm resulted in significant disruption of the bilateral sensory network, increased network global efficiency, and decreased network modularity.